1998
DOI: 10.1007/s001250051009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma phospholipid transfer protein activity is related to insulin resistance: impaired acute lowering by insulin in obese Type II diabetic patients

Abstract: Among other factors, high density lipoprotein (HDL) metabolism and remodelling is governed by cholesteryl ester transfer protein (CETP) and phospholipid transfer protein (PLTP) [1±7]. CETP catalyses the transfer of cholesteryl esters (CE), triglycerides (TG) and phospholipids between HDL and very low + low density lipoproteins (VLDL + LDL). PLTP specifically facilitates the transfer of phospholipids between lipoproteins and is able to convert HDL 3 into small and large HDL particles [5]. During this HDL remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
96
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 23 publications
11
96
4
Order By: Relevance
“…Similarily, for type 2 diabetic patients unchanged, 19,20 decreased 17,18 and accelerated CETP activities 22 have been reported. In hyperinsulinemic euglycemic clamp studies 19,20 decreased PLTP activity after insulin infusion was reported in both, healthy and type 2 diabetic subjects. Similar results were found in a hyperglycemia-induced hyperinsulinemia study in healthy humans.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarily, for type 2 diabetic patients unchanged, 19,20 decreased 17,18 and accelerated CETP activities 22 have been reported. In hyperinsulinemic euglycemic clamp studies 19,20 decreased PLTP activity after insulin infusion was reported in both, healthy and type 2 diabetic subjects. Similar results were found in a hyperglycemia-induced hyperinsulinemia study in healthy humans.…”
Section: Introductionsupporting
confidence: 80%
“…14 -16 In several clinical studies the influence of insulin infusion on lipid transfer protein activities was investigated with, however, partly conflicting results. 17 -21 In healthy subjects insulin infusion appeared not to change CETP activity in some studies, 18,20,21 while in others 13,19 it decreased CETP activity. Similarily, for type 2 diabetic patients unchanged, 19,20 decreased 17,18 and accelerated CETP activities 22 have been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study we have found that overall phospholipid transfer tended to be lower in the diabetic subjects than in controls, but whereas cholesteryl ester transfer increased postprandially phospholipid transfer decreased. The postprandial fall in PLTP activity is unexplained but likely be related to insulin sensitivity [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…These changes could be mediated by cholesteryl Hyperinsulinemia, adipocyte and erythrocyte phospholipids N Zeghari et al ester transfer protein (CETP), which has a role in the selective uptake of HDL cholesteryl esters by human adipocytes, 42 or by phospholipid transfer protein (PLTP). 43 CETP and PLTP activities are elevated in obesity 44 and in insulin resistance 45 as well as the HDL binding to adipocytes. 19 The hormone status may be also important.…”
Section: Discussionmentioning
confidence: 99%